2015
DOI: 10.3109/10242422.2015.1083015
|View full text |Cite
|
Sign up to set email alerts
|

Nitrile-metabolizing potential ofBacilluscereus strain FA12; Nitrilase production, purification, and characterization

Abstract: Nitrile-hydrolyzing bacteria have the potential to perform useful biotransformations such as the production of industrially useful acids and amides. In this study, we report a nitrile-degrading bacterium with signifi cant nitrile metabolism. Molecular characterization of 16S rDNA gene characterized this strain as Bacillus cereus . Medium optimization of B. cereus FA12 showed that biomass and nitrilase production was strongly supported by glucose (10 gL Ϫ 1 ) and yeast extract (10 gL Ϫ 1 ). Enzymatic production… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…The apparent molecular mass of the purified RZ44 nitrilase as obtained by SDS-PAGE is about 30 kDa ( Figure 4 ). The molecular weights of nitrilase from other bacterial species have been reported as 45 kDa for Bacillus cereus strain FA12 ( 41 ), 43 kDa for Pseudomonas putida ( 42 ), and 33 kDa for P. fluorescens Pf5 ( 23 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The apparent molecular mass of the purified RZ44 nitrilase as obtained by SDS-PAGE is about 30 kDa ( Figure 4 ). The molecular weights of nitrilase from other bacterial species have been reported as 45 kDa for Bacillus cereus strain FA12 ( 41 ), 43 kDa for Pseudomonas putida ( 42 ), and 33 kDa for P. fluorescens Pf5 ( 23 ).…”
Section: Resultsmentioning
confidence: 99%
“…It was also revealed that the quantity of acrylic acid and acetic acid identified from the conversion of the correspond nitrile is maximum after 4 and 6 hours of incubation with acrylonitrile and acetonitrile, respectively. The time course of acetonitrile (3.5 mM) and acrylonitrile (5 mM) conversion into their corresponding acids by B. cereus FA12 resting cells showed that these nitriles were hydrolyzed within 12 h, and the amount of ammonia produced from acetamide and acetonitrile was maximum after 5 and 7 hours of the incubation, respectively ( 41 ). Remarkably, the quantity of the acetic and acrylic acids identified from the conversion of acetonitrile and acrylonitrile showed a small aberration from the theoretical quantity which was equivalent to the quantity of acetonitrile and acrylonitrile added (3.5 and 5 mM, respectively).…”
Section: Discussionmentioning
confidence: 99%
“…Another important observation arising from our experiments is that zinc oxide nanoparticles influence metabolic processes in Bacillus which are important for the biotransformation of various compounds. B. cereus is capable of decomposing anthropogenic pollutants, including azo dyes, nitriles, and pesticides such as beta-cypermethrin and pentachlorophenol [ 78 , 79 , 80 ]. It also plays an important role in the environment by breaking down natural complex chemical compounds such as resveratrol or polyphenolic compounds [ 58 , 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…M24D13 and optimum activity was determined at 85 °C. Ramezani‐Pour et al reported nitrile metabolizing isolate Bacillus cereus strain FA12 for nitrilase activity at 40 °C. Chen et al reported Clostridium thermocellum nitrilase expressed on Bacillus subtilis spores and this recombinant nitrilase catalyzed the conversion of 3‐cyanopyridine to niacin and displayed maximum catalytic activity (8.22 U mg −1 protein) at 40 °C and pH 7.4.…”
Section: Discussionmentioning
confidence: 99%